FACTORS ASSOCIATED WITH THE ADOPTION OF FERTILIZER APPLICATION IN YENAGOA LOCAL GOVERNMENT AREA OF THE RIVERS STATE, NIGERIA. - JIBOWO , A. A.; FRANCIS, T. M. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
An investigation was conducted to identify the personal, social. economic, psychological and physical factors associated with the adoption of fertilizer application practices in Yenagoa Local Government Area, Rivers State of Nigeria. Data were collected from 78 adopters and 68 non-adopters of the practice in October and November 1988. Significant associations were found between adoption and literacy, membership in organization, contact with extension agents, income, attitude toward fertilizer application moderators. Farmers with the identified characteristics would be expected to respond more favourably to a fertilizer campaign than their counterparts with less of these attributes